Regional Economic Outlook, May 2013, Sub-Saharan Africa : Building Momentum in a Multi-Speed World. (Regional Economic Outlook, 2013)
Growth remained strong in the region in 2012, with regional GDP rates increasing in most countries (excluding Nigeria and South Africa). Projections point to a moderate, broad-based acceleration in growth to around 5 1\2 percent in 2013-14, reflecting a gradually strengthening global economy and robust domestic demand. Investment in export-oriented sectors remains an important economic driver, and an agriculture rebound in drought-affected areas will also help growth. Uncertainties in the global economy are the main risk to the region's outlook, but plausible adverse shocks would likely not have a large effect on the region's overall performance.